Endoscopic Management of Benign Colonic Obstruction and Pseudo-Obstruction - Su Jin Jeong; Jongha Park (Korean Society of Gastrointestinal Endoscopy, 2020)
There are a variety of causes of intestinal obstruction, with the most common cause being malignant diseases; however, volvulus, inflammatory bowel disease or diverticulitis, radiation injury, ischemia, and pseudo-obstruction can also cause colonic obstruction. These are benign conditions; however, delayed diagnosis of acute intestinal obstruction owing to these causes can cause critical complications, such as perforation. Therefore, high levels of clinical suspicion and appropriate treatment are crucial. There are variable treatment options for colonic obstruction, and endoscopic treatment is known to be a less invasive and an effective option for such. In this article, the authors review the causes of benign colonic obstruction and pseudo-obstruction and the role of endoscopy in treating them.